THE IMPACT OF STEAM APPROACHES ON STUDENT LEARNING OUTCOMES AND CREATIVITY: A SYSTEMATIC LITERATURE REVIEW - Evika Widya Puspita; Putri Yanuarita Sutikno; Ellianawati Ellianawati; Fahrur Rozi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid advancement of science, technology, engineering, arts, and mathematics (STEAM) in the 21st century has reshaped educational paradigms, emphasizing creativity and interdisciplinary learning. However, variations in implementation have led to inconsistent findings regarding its effectiveness. This study aims to systematically review and synthesize empirical research published between 2021 and 2025 on the impact of STEAM approaches on students’ learning outcomes and creativity. Employing a Systematic Literature Review (SLR) method guided by the PRISMA protocol, the review involved four main stages: identification, screening, eligibility, and inclusion across Crossref, Scopus, and Google Scholar databases. A total of 1,344 articles were retrieved, and 38 met the inclusion criteria for analysis. The results indicate that STEAM education enhances cognitive, affective, and psychomotor learning while fostering creativity through the integration of the arts, encouraging originality and innovation. It is concluded that STEAM serves as a holistic pedagogical framework that bridges academic achievement and creativity, preparing adaptive and innovative learners for 21st-century challenges.